Geo-Informatics in Resource Management and Sustainable Ecosystem International Symposium, GRMSE 2013, Wuhan, China, November 8-10, 2013, Proceedings, Part II - Bian, Fuling; Xie, Yichun; Cui, Xiaohui; Zeng, Yixin; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This two volume set (CCIS 398 and 399) constitutes the refereed proceedings of the International Symposium on Geo-Informatics in Resource Management and Sustainable Ecosystem, GRMSE 2013, held in Wuhan, China, in November 2013. The 136 papers presented, in addition to 4 keynote speeches and 5 invited sessions, were carefully reviewed and selected from 522 submissions. The papers are divided into 5 sessions: smart city in resource management and sustainable ecosystem, spatial data acquisition through RS and GIS in resource management and sustainable ecosystem, ecological and environmental data processing and management, advanced geospatial model and analysis for understanding ecological and environmental process, applications of geo-informatics in resource management and sustainable ecosystem.
Smart city in resource management and sustainable ecosystem -- Spatial data acquisition through RS and GIS in resource management and sustainable ecosystem -- Ecological and environmental data processing and management -- Advanced geospatial model and analysis for understanding ecological and environmental process -- Applications of geo-informatics in resource management and sustainable ecosystem.
Keywords: Computer science; Remote sensing; Software engineering; Computer system performance; Computer simulation; Computer Science; Special Purpose and Application-Based Systems; System Performance and Evaluation; Simulation and Modeling; Remote Sensing/Photogrammetry.